Unseen threats: negative effects of microplastic leachate on coral planulae settlement - Wilkins, Keiko W.; Richmond, Robert H. (Frontiers in Marine Science, 2025)
Coral reef ecosystems, especially those in Hawai`i, are increasingly threatened by marine plastic pollution, which may impair coral reproduction. Microplastics contain toxic, persistent, and endocrine-disrupting chemicals. While negative effects of microplastic ingestion have been observed on adult coral viability and health, very few studies have explored impacts on reproduction. Recent studies found that microplastic leachate negatively affects coral fertilization likely due to plastic additives incorporated into products during manufacturing. This study explored the effects of microplastic leachate on coral planula larvae settlement and survival. Planula larvae of the broadcast spawning species, Montipora capitata, and the brooding species, Harbor Porites, were exposed to microplastic leachate from four plastic types [nylon, polypropylene (PP), high-density polyethylene (HDPE), or low-density polyethylene (LDPE)] at three concentrations (50, 100, or 200 particles/L) for 7 days. Settlement and survival were affected by leachate concentration and polymer type strongly on Days 5 and 7 indicating delayed and/or potentially cumulative effects. The most pronounced negative effects on survival were observed with HDPE—100 and LDPE—200 treatments. One treatment unexpectedly promoted settlement (HDPE—200) likely due to attractive chemical cues released by the leachates. This is particularly concerning, as it suggests that planula larvae may be drawn to settle on degraded or suboptimal substrates affecting reef recruitment and replenishment. Species-specific responses were also found, with Harbor Porites exhibiting higher survival and variable settlement. Overall, microplastic leachate significantly impacted survival and settlement of both Montipora capitata and Harbor Porites planula larvae with complex temporal, species-specific, polymer-type, and concentration-dependent effects. Microplastic leachate presents an additional stressor to already threatened coral species making addressing both local and global stressors critical for the protection of coral reef ecosystems.